Riemann's ζ\zeta Function and Prime Numbers

We know that π26=112+122+132+122×π26=122×112+122×122+122×132+122×π26=122+142+162+(1122)π26=112+132+152+34×π26=112+132+152+π28=112+132+152+π224=122+142+162+(18124)π2=112122+132π212=112122+132\begin{aligned} \because \dfrac{\pi^2}{6} &=\dfrac{1}{1^2}+\dfrac{1}{2^2}+\dfrac{1}{3^2}+\cdots \\ \therefore \dfrac{1}{2^2} \times \dfrac{\pi^2}{6} &=\dfrac{1}{2^2} \times \dfrac{1}{1^2}+\dfrac{1}{2^2} \times \dfrac{1}{2^2}+\dfrac{1}{2^2} \times \dfrac{1}{3^2}+\cdots \\ \therefore \dfrac{1}{2^2} \times \dfrac{\pi^2}{6} &=\dfrac{1}{2^2}+\dfrac{1}{4^2}+\dfrac{1}{6^2}+\cdots \\ \therefore (1-\dfrac{1}{2^2})\dfrac{\pi^2}{6} &=\dfrac{1}{1^2}+\dfrac{1}{3^2}+\dfrac{1}{5^2}+\cdots \\ \dfrac{3}{4} \times \dfrac{\pi^2}{6} &=\dfrac{1}{1^2}+\dfrac{1}{3^2}+\dfrac{1}{5^2}+\cdots \\ \therefore \dfrac{\pi^2}{8} &=\dfrac{1}{1^2}+\dfrac{1}{3^2}+\dfrac{1}{5^2}+\cdots \\ \dfrac{\pi^2}{24} &=\dfrac{1}{2^2}+\dfrac{1}{4^2}+\dfrac{1}{6^2}+\cdots \\ \therefore (\dfrac{1}{8}-\dfrac{1}{24})\pi^2 &=\dfrac{1}{1^2}-\dfrac{1}{2^2}+\dfrac{1}{3^2}-\cdots \\ \therefore \dfrac{\pi^2}{12} &=\dfrac{1}{1^2}-\dfrac{1}{2^2}+\dfrac{1}{3^2}-\cdots \\ \end{aligned} As for π26=112+122+132+\dfrac{\pi^2}{6}=\dfrac{1}{1^2}+\dfrac{1}{2^2}+\dfrac{1}{3^2}+\cdots, let zz takes 22's place, we can get the Riemann's ζ\zeta function. And if we continue, we can get ζ(z)=11z+12z+13z+(112z)ζ(z)=11z+13z+15z+13z×(1122)ζ(z)=13z×11z+13z×13z+13z×15z+(113z)(112z)ζ(z)=11z+15z+17z+(115z)(113z)(112z)ζ(z)=11z+17z+111z+1=ζ(z)(112z)(113z)(115z)ζ(z)=1(112z)(113z)(115z)(117z)\begin{aligned} \zeta(z) &=\dfrac{1}{1^z}+\dfrac{1}{2^z}+\dfrac{1}{3^z}+\cdots \\ (1-\dfrac{1}{2^z})\zeta(z) &=\dfrac{1}{1^z}+\dfrac{1}{3^z}+\dfrac{1}{5^z}+\cdots \\ \therefore \dfrac{1}{3^z} \times (1-\dfrac{1}{2^2})\zeta(z) &=\dfrac{1}{3^z} \times \dfrac{1}{1^z}+\dfrac{1}{3^z} \times \dfrac{1}{3^z}+\dfrac{1}{3^z} \times \dfrac{1}{5^z}+\cdots \\ \therefore (1- \dfrac{1}{3^z}) (1-\dfrac{1}{2^z})\zeta(z) &=\dfrac{1}{1^z}+\dfrac{1}{5^z}+\dfrac{1}{7^z}+\cdots \\ \therefore (1-\dfrac{1}{5^z})(1- \dfrac{1}{3^z}) (1-\dfrac{1}{2^z})\zeta(z) &=\dfrac{1}{1^z}+\dfrac{1}{7^z}+\dfrac{1}{11^z}+\cdots \\ \therefore 1 &=\zeta(z)(1-\dfrac{1}{2^z})(1- \dfrac{1}{3^z})(1-\dfrac{1}{5^z})\cdots \\ \therefore \zeta(z) &=\dfrac{1}{(1-\dfrac{1}{2^z})(1- \dfrac{1}{3^z})(1-\dfrac{1}{5^z})(1-\dfrac{1}{7^z})\cdots} \end{aligned}

Note by Edward Christian
4 weeks ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

There are no comments in this discussion.

×

Problem Loading...

Note Loading...

Set Loading...